Molecular characterization of a fimbrial adhesin, F1845, mediating diffuse adherence of diarrhea-associated Escherichia coli to HEp-2 cells. - Bilge, S S (1989)
A fimbrial adhesin, designated F1845, was found to be responsible for the diffuse HEp-2 cell adherence of a diarrheal Escherichia coli isolate. The genetic determinant of F1845 was cloned, and the order of the genes necessary for production of F1845 was determined by maxicell analysis. Five polypeptides with apparent sizes of 10, 95, 27, 15.5, and 14.3 kilodaltons (kDa) were found to be encoded in that order by the F1845 determinant. The nucleotide sequence of the 14.3-kDa subunit gene was determined and found to share extensive homology in its signal sequence with the gene encoding the structural subunit of the AFA-1 hemagglutinin of a uropathogenic E. coli strain (A. Labigne-Roussel, M.A. Schmidt, W. Walz, and S. Falkow, J. Bacteriol. 162:1285-1292, 1985) but not in the region encoding the mature protein. Southern blot hybridizations indicated that the F1845 determinants are of chromosomal origin. Hybridization studies using a probe from the region encoding the 95-kDa polypeptide indicated that related sequences may be plasmid associated in some strains and chromosomal in others. Additional hybridization studies of E. coli isolates possessing sequence homology to the F1845 determinant suggest that the sequences in the 5' region of the F1845 structural subunit gene are more highly conserved than sequences in the 3' region.